407 Anterior Cervical Discectomy and Fusion in Ambulatory Surgery Center Versus Hospital Setting: One-Year Cost Utility and Cost Benefit Analysis. (April 2023) - Hani, Ummey; Monk, Steve Hubert; Pfortmiller, Deborah; Adamson, Tim E.; Bohl, Michael; Kim, Paul Keetae; Holland, Christopher Michael; McGirt, Matthew J.
Abstract : INTRODUCTION: Outpatient anterior cervical discectomy and fusion (ACDF) has recently gained popularity due to improved care and reduced costs. Cost-utility studies for ambulatory vs. inpatient ACDF are largely limited to small series, precluding an accurate assessment of cost-effectiveness. METHODS: A 6, 504, ASA 1-3, patient sample (520 ASC, 5, 984 inpatient) was used to propensity-match 748 patients (374/cohort) undergoing 1-2-level ACDF. Data was queried from the National Quality Outcomes Database (QOD). Medical resource utilization, missed work, and quality adjusted life years (QALYs) were assessed. Direct cost (one-year resource use x unit costs based on Medicare national allowable payment amounts) and indirect cost (missed workdays x average US daily wage) were recorded and incremental cost-effectiveness ratio was calculated. RESULTS: Estimated blood loss, length of surgery, and hospitalization were less for ASC vs. inpatient ACDF (p < 0.001). ASC vs. inpatient ACDF demonstrated similar improvement in patient reported outcomes. ASC vs. inpatient ACDF was associated with lower total one-year cost of $5, 879.46 for Medicare patients and $12, 873.97 for private payers (p < 0.001), with similar QALYs gained. Hospital vs ASC had a highly cost ineffective ICER of $3, 674, 662.50/QALY-gained and $8, 046, 231.25/QALY for Medicare and private payer patients, respectively. CONCLUSIONS: 1-2-level ACDF in the hospital vs ASC is associated with increased mean costs, without a QALY, safety, or outcome benefit. Hence, health economics strongly favor the ASC setting to the hospital for ACDF.